2016
DOI: 10.1109/tcad.2015.2504875
|View full text |Cite
|
Sign up to set email alerts
|

Workload Change Point Detection for Runtime Thermal Management of Embedded Systems

Abstract: Abstract-Applications executed on multicore embedded systems interact with system software (such as the OS) and hardware, leading to widely varying thermal profiles which accelerate some aging mechanisms, reducing the lifetime reliability. Effectively managing the temperature therefore requires (1) autonomous detection of changes in application workload and (2) appropriate selection of control levers to manage thermal profiles of these workloads. In this paper we propose a technique for workload change detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Recent research efforts have focused on how to improve this architecture. Methods include: enabling more performance counters to build complex system features [19] [20] [27], using powerful models for prediction [19] [18] [20] [21] [24], designing better control rules [19] [18] [20] [21], or learning control policy based on reinforcement learning [24] [25] [26] [27] [30].…”
Section: Problem Statement and Proposed Approachmentioning
confidence: 99%
“…Recent research efforts have focused on how to improve this architecture. Methods include: enabling more performance counters to build complex system features [19] [20] [27], using powerful models for prediction [19] [18] [20] [21] [24], designing better control rules [19] [18] [20] [21], or learning control policy based on reinforcement learning [24] [25] [26] [27] [30].…”
Section: Problem Statement and Proposed Approachmentioning
confidence: 99%
“…Using this framework, authors propose to distribute neurons and synapses to different crossbars of a hardware such that the average temperature of different crossbars is reduced, which in turn improves reliability [157]. The thermal formulation incorporates both the temporal component, resulting from self-heating of a PCM cell over time due to propagating spikes of a machine learning workload and the spatial component, resulting from heat transfer from nearby cells within a crossbar [158,159,160,161,162,163,164]. The thermal formulation is integrated inside a Hill-Climbing heuristic, which is used to map neurons and synapses to different crossbars of a hardware.…”
Section: System Software For Thermal and Reliability Optimizationmentioning
confidence: 99%
“…Each study in [6,8,13,15,25,26] considered different heat sources, but all studies use thermal prediction methods in their proactive DTM. Das et al [27,28] reported that their proactive run-time manager using reinforcement learning reduces thermal overheads, such as average temperature, peak temperature, and thermal cycling. The authors of [9,11] proposed DTM techniques using the power budget given by thermal prediction.…”
Section: Dynamic Thermal Management For Mobile Devicesmentioning
confidence: 99%
“…The constraint in Equation (28) says that each application's QoS should be guaranteed as higher than the minimum user required QoS u min a i at all times. The constraint in Equation (29) constrains that each application a i should be mapped to only one core out of {c 2 , c 3 , • • • , c C }.…”
Section: Problem Formulationmentioning
confidence: 99%